New online assessment among IIUM preclinical medical students: a firsthand experience - Mat Harun, Noraihan; Mohd Noor, Mohd Fadly; Ismail, Soraya; Mohd Zainudin, Maizura; Hamzah, Hairul Aini; Abdul Rahim, Roslina; Khaing, Aye Thi; Mohd Radzuan, Hazulin; Ismawi, Hidayatul Radziah; Abd. Rahim, Nour El Huda; Mohamed Bakrim, Norbaiyah; Wan Omar, Wan Fatein Nabeila; et al. (2021)
This was a poster submitted to the International Putra Innovative Teaching and Learning (PicTL) 2020 poster competition from 22-30 October 2020, organized by University Putra Malaysia. It reported on the IIUM preclinical medical students experience during the synchronous online assessment using iTa'leEM Quiz for the academic year 2019-2020. This poster won a Bronze Medal Award.